Finite element analysis of damage mechanisms of composite wind turbine blade by considering fluid/solid interaction. Part I: Full-scale structure. (1st December 2022) - Liu, J.W.; Liu, P.F.; Leng, J.X.; Wang, C.Z.
Abstract: This paper is the first one of two that studies damage mechanisms of composite wind turbine blade using numerical analysis. An important highlight is to consider fully complex failure modes of the skin and web as well as the adhesive failure between them. The main work is divided into three parts: (1) the damage model for composite laminates developed by our research group is applied to the skin and web, and the bilinear cohesive model is used to predict the adhesive failure; (2) finite element model is established by considering fluid/solid interaction to study damage mechanisms of a 59.5 m long blade; (3) the wind velocity model including the normal and extreme wind shear effects as well as the tower shadow effect is considered for fluid elements as boundary conditions. By performing fluid/solid coupling analysis using ABAQUS software, distributions of the stress, displacement and damage for the skin, web and adhesive layer as well as the fluid field information under different wind velocity are explored. In addition, numerical results are also compared with those using the blade element momentum (BEM) theory and other existing work. Some conclusions for predicting damage mechanisms and suggestions for improving damage tolerance and load-bearing ability of the blade are given.